2021 Annual Reliability and Maintainability Symposium (RAMS) 2021
DOI: 10.1109/rams48097.2021.9605705
|View full text |Cite
|
Sign up to set email alerts
|

Cascade Effect Analysis in Torrential Context for Prioritizing Check Dams Maintenance Strategies

Abstract: Natural hazards in mountains pose threat to people, properties, and infrastructures. Several mitigation strategies aim to reduce the induced risk and to protect vulnerable issues exposed to such dangerous phenomena. Check dams are one type of structural protection measures constructed in series along mountain streams. They constitute a critical interdependent multi-component system that deteriorates over time and requires regular inspection and maintenance. The propagation of damage is influenced by failure de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Other studies were presented in the 60th ESReDA seminar to analyze infrastructure resilience against natural hazards. 30 Also, the resilience of deteriorating debris maintenance System has been modeled by Chahrour et al 31 This study provides a decision-making model to help in the maintenance of systems In general, simulation methods require a lot of time, high cost, and extensive technical, operational, and organizational information and data. Therefore, the implementation of these methods is limited to organizations that have such characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies were presented in the 60th ESReDA seminar to analyze infrastructure resilience against natural hazards. 30 Also, the resilience of deteriorating debris maintenance System has been modeled by Chahrour et al 31 This study provides a decision-making model to help in the maintenance of systems In general, simulation methods require a lot of time, high cost, and extensive technical, operational, and organizational information and data. Therefore, the implementation of these methods is limited to organizations that have such characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…The main objective of the adaptation was to reduce maintenance costs while maintaining a satisfying protection efficacy. Chahrour et al (2022) developed an integrated approach to optimize maintenance strategies in the case of the initial design of the Claret's retention dam considering only the costs of maintenance. The performed analysis revealed that waiting until the debris basin is almost completely filled, and then cleaning all the stored volume is the mostcost effective strategy.…”
Section: Introductionmentioning
confidence: 99%
“…The main objective of the adaptation was to reduce maintenance costs while maintaining a satisfying protection efficacy. Chahrour et al (2022) developed an integrated approach to optimize maintenance strategies in the case of the initial design of the Claret's retention dam considering only the costs of maintenance. The performed analysis revealed that waiting until the debris basin is almost completely filled, and then cleaning all the stored volume is the mostcost effective strategy.…”
Section: Introductionmentioning
confidence: 99%